2013
DOI: 10.1016/j.cca.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Plasma globotriaosylsphingosine (lysoGb3) could be a biomarker for Fabry disease with a Chinese hotspot late-onset mutation (IVS4+919G>A)

Abstract: Plasma lysoGb3 is a more sensitive and reliable biomarker than plasma Gb3. LysoGb3 also correlated with age and left ventricular mass index in Fabry patients with IVS4+919G>A mutation. Because lots of infants with the IVS4+919G>A mutation already had elevated lysoGb3 levels at birth, that indicates that the development of hypertrophic cardiomyopathy may require a long and insidious course after lysoGb3 accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
2
26
2
Order By: Relevance
“…This widely diffusible lyso-Gb 3 might have the capacity to induce cell damage via some mechanism that we do not yet understand well. Interestingly, in a previous study on our IVS4 patients, we also found only lyso-Gb 3 levels, not Gb 3 , elevated in our symptomatic male and female patients, and these lyso-Gb 3 levels also appeared to positively correlate with the severity of cardiac manifestations (Liao et al 2013). Since we found that serum lysoGb 3 can be elevated in both male and female infants, does this mean that cardiac manifestations are induced after a long and insidious course of elevated lyso-Gb 3 ?…”
Section: Discussionsupporting
confidence: 66%
“…This widely diffusible lyso-Gb 3 might have the capacity to induce cell damage via some mechanism that we do not yet understand well. Interestingly, in a previous study on our IVS4 patients, we also found only lyso-Gb 3 levels, not Gb 3 , elevated in our symptomatic male and female patients, and these lyso-Gb 3 levels also appeared to positively correlate with the severity of cardiac manifestations (Liao et al 2013). Since we found that serum lysoGb 3 can be elevated in both male and female infants, does this mean that cardiac manifestations are induced after a long and insidious course of elevated lyso-Gb 3 ?…”
Section: Discussionsupporting
confidence: 66%
“…The preparation and analysis of the samples was described in our previous publication [13]. Control samples were obtained from 31 healthy adults (16 males and 15 females).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies revealed that globotriaosylsphingosine (lyso-Gb3) has high diagnostic sensitivity and correlates with left ventricular mass (LVM), taking into account gender and age in our late-onset Fabry patients [13]. However, its use as a biomarker to monitor the therapeutic outcome of enzyme replacement therapy (ERT) has not been carefully evaluated in our late-onset Fabry patients.…”
Section: Introductionmentioning
confidence: 99%
“…50 Another disease biomarker detectable in blood is globotriaosylsphingosine, but its usefulness in the neonatal period and in the context of NBS requires more study. [51][52][53] ERT became available for Fabry disease treatment in the early 2000s, leading to significant improvements unless irreversible damage has already occurred. Accordingly, early detection of Fabry disease through NBS is expected to dramatically improve the outcome of affected patients.…”
Section: Newborn Screening For Fabry Diseasementioning
confidence: 99%